The Effect of Emotional Intelligence and Work Environment On Affective Commitment and Job Satisfaction as Intervening Variables in State Elementary School 1 In Kemayoran District, Central Jakarta - Dimas Bayu; Dewi Susita; Widya Parimita (The Institute of Academic Research and Publication (IARP), 2023)
This study aims to determine the effect of emotional intelligence and the work environment on affective commitment and job satisfaction as intervening variables in State Elementary School 1 in Kemayoran District, Central Jakarta. This study used a quantitative research type using a population of 214 teachers from 11 State Elementary Schools in Kemayoran District, Central Jakarta. The sample used in this study amounted to 102 people. Data collection techniques using questionnaires, observation and literature study. Data analysis used Partial Least Square (PLS) analysis using SmartPls version 3.0. The results of this study indicate that emotional intelligence has a direct effect on job satisfaction in Teachers. The work environment has a direct effect on job satisfaction in Teachers. Job satisfaction has a direct effect on affective commitment in Teachers. Emotional intelligence has a direct effect on affective commitment in Teachers. The work environment does not directly affect affective commitment in Teachers. Emotional intelligence does not directly influence Teachers' affective commitment with job satisfaction as an intervening variable. The work environment directly influences Teachers affective commitment with job satisfaction as an intervening variable.